Empirical Analysis of the Determinants of Trade Balance in Post-liberalization Ghana. Issue 3 (August 2019) - Akoto, Linda; Sakyi, Daniel
This study investigates the determinants of trade balance in post-liberalization Ghana, covering the period 1984–2015. Specifically, we test the validity of the Marshall-Lerner condition and the J-curve effect, and further assess the effect of other macroeconomic variables including household consumption expenditure, government consumption expenditure, foreign income, money supply and domestic prices on trade balance. The bounds testing approach to cointegration and the error correction model within a symmetric and asymmetric autoregressive distributed lag (ARDL) framework is used for the estimation. Additionally, to analyse the dynamic interactions of the variables included in the estimated model, variance decomposition is applied. The results from both symmetric and asymmetric specifications show the absence of the Marshall-Lerner condition and the J-curve effect. Further, the study finds that household consumption expenditure, government consumption expenditure and domestic prices are negative and significant in the long and short run, whereas foreign income and money supply are positive and significant in the short run. Results from the variance decomposition show that innovations in household consumption expenditure highly contribute to the forecast error variance of the trade balance compared with other explanatory variables. A key finding of the study suggests that depreciation of the Ghana cedi is not an appropriate step to help in improving the country's trade balance position. JEL Codes: C22, F10, F31, F32